Bee pollen from babaçu (Attalea speciosa Mart. ex Spreng.) forest (Research, Society and Development, 2020)
The objective was to describe the potential of babassu forests (Attalea speciosa Mart. Ex Spreng.) To produce bee pollen, as well as to determine the nutritional composition of the product. For this purpose, pollen collectors were installed in hives of Africanized bees (Apis mellifera L.) from the Experimental Apiary of the Zootechnical Practices Center of the Instituto de Ensino Superior Múltiplo, in the municipality of Timon, Maranhão. Pollen samples from each hive were collected daily during the first week of each month during the babassu flowering periods and taken to an electric oven. Subsequently, they were cleaned, placed in plastic bags, separated by date of collection. The predominance of the pollen type regarding babassu was investigated, and the samples from that palm were weighed and subjected to the evaluation of crude protein content and the amount of amino acids. It was observed that only the pollen sample referring to the collection carried out in October was considered monofloral (51.8 g/hive) and the occurrence of babassu pollen gradually decreased until its disappearance in the collected samples. Regarding nutritional composition, although the protein content (23.12%) was considered similar and many times higher than that found in the literature, the amounts of essential amino acids partially supplied the nutritional requirements of the bees, which may have influenced the behavior foraging these insects in babassu forests.